2011
DOI: 10.1088/1741-2560/8/4/046006
|View full text |Cite
|
Sign up to set email alerts
|

Automatic subthalamic nucleus detection from microelectrode recordings based on noise level and neuronal activity

Abstract: Microelectrode recording (MER) along surgical trajectories is commonly applied for refinement of the target location during deep brain stimulation (DBS) surgery. In this study, we utilize automatically detected MER features in order to locate the subthalamic nucleus (STN) employing an unsupervised algorithm. The automated algorithm makes use of background noise level, compound firing rate and power spectral density along the trajectory and applies a threshold-based method to detect the dorsal and the ventral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…During surgery the entrance and exit of STN were discerned visually by the neurophysiologist as an increase and decrease, respectively, in the background noise amplitude and neuronal firing [18,29,39]. In this way, each MER point was classified to be inside or outside the STN.…”
Section: Fitting An Atlas Stn To Mermentioning
confidence: 99%
“…During surgery the entrance and exit of STN were discerned visually by the neurophysiologist as an increase and decrease, respectively, in the background noise amplitude and neuronal firing [18,29,39]. In this way, each MER point was classified to be inside or outside the STN.…”
Section: Fitting An Atlas Stn To Mermentioning
confidence: 99%
“…This corresponds with a clinically more alert patient, but it is unknown whether the neural activity remains suppressed. In this study, the MER measures examined here are those typically taken and used intraoperatively, such as RMS power assessment as a marker of background population activity, STN pass length in millimeters (determined by a clear background activity change consistent with STN activity), and the number of passes that yielded STN [9,11,22,23,24,25]. In addition, to help adjunct the results of the study by Krishna et al [21], we also analyze measures of STN unit activity, such as spike frequency (Hz) and the variability of firing activity (i.e., is the pattern or “burstiness” of firing changed by the addition of DEX).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to help adjunct the results of the study by Krishna et al [21], we also analyze measures of STN unit activity, such as spike frequency (Hz) and the variability of firing activity (i.e., is the pattern or “burstiness” of firing changed by the addition of DEX). Although these single-neuron electrophysiological measures are not commonly used intraoperatively due to the difficulty of processing online, they are increasingly hypothesized to be of use to help delineate proper targeting within the STN [23,26,27,28]. While this is a retrospective analysis, we feel that these data may provide important qualitative and quantitative measures of the effect of DEX on MER recordings performed during STN-DBS surgery in the real-world Parkinsonian patient.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, MER signals are observed both visually and with audio by the physiologist and/or neurosurgeon during surgery to identify the functional targets. Recently, several studies have shown that MER data can be utilized for automatic localization of the STN with reduced variation and better accuracy [25,26,27,28,29,30]. Commonly used signal features include the background noise level, spike count and power spectral density (PSD) in the beta and theta (tremor) frequency bands.…”
Section: Introductionmentioning
confidence: 99%